2017
DOI: 10.1097/ico.0000000000001368
|View full text |Cite
|
Sign up to set email alerts
|

Donor Tissue Preparation for Descemet Membrane Endothelial Keratoplasty: An Updated Review

Abstract: An overview of the current harvesting techniques available for DMEK may benefit corneal surgeons and eye banks in choosing the best approach for each specific user.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
2
34
0
1
Order By: Relevance
“…Moreover, the endothelial cells were preserved better after the liquid bubble technique. However, other studies reported the contrary result that manual stripping technique was similar or better than liquid bubble technique . Nevertheless, the success rates were similar between the 2 techniques, so it is hard to judge which technique is more reliable and suitable for porcine corneas.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, the endothelial cells were preserved better after the liquid bubble technique. However, other studies reported the contrary result that manual stripping technique was similar or better than liquid bubble technique . Nevertheless, the success rates were similar between the 2 techniques, so it is hard to judge which technique is more reliable and suitable for porcine corneas.…”
Section: Discussionmentioning
confidence: 93%
“…However, other studies reported the contrary result that manual stripping technique was similar or better than liquid bubble technique. 32,33 Nevertheless, the success rates were similar between the 2 techniques, so it is hard to judge which technique is more reliable and suitable for porcine 35 Considering that, we investigated the correlation in the porcine DM, and the result also indicated the same tendency. However, the porcine DMEK rolls came from WZS-pigs with different ages were all triangle-shaped, and the tightness of the rolls did not vary with their thickness.…”
Section: Wzs-24# 21 18mentioning
confidence: 98%
“…There are several graft excision techniques that have been published in literature with advantages and disadvantages as recently reviewed and reported by Birbal et al. (). The limitation of this study was that we were only able to get data on five techniques that are routinely prepared by our eye bank and collaborators.…”
Section: Discussionmentioning
confidence: 99%
“…Using preprepared tissue may, therefore, facilitate smoother surgery. As there are several possible techniques for DMEK graft preparation (Birbal et al 2018), we studied few methods that are routinely used and compared them to find out the most suitable technique for DMEK graft preparation. Hence, we selected three different ways of stripping and two bubble techniques and compared multiple parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation